Simultaneous in vivo dynamic magnetic resonance-diffuse optical tomography for small animal imaging - Unlu, Mehmet Burcin (2008)
We present simultaneous measurement of enhancement kinetics of an optical and a magnetic resonance (MR) contrast agent in a small animal breast tumor model (R3230 ac) using a combined MR-diffuse optical tomographic (MR-DOT) imaging system. A mixture of a small molecular-weight MR contrast agent gadolinium-diethylene-triamine-pentaacetic acid (Gd-DTPA) and a large molecular-weight optical contrast agent indocyanine green (ICG) was administered intravenously for multimodal dynamic imaging. Coregistration of optical and MR images was accomplished using agar-water–based markers. Using T(2) and dynamic T(1) weighted MR images, we divided the entire tumor into two regions of interest (ROI): a viable and a nonviable region. The absorption enhancements in the ROIs were calculated. An enhancement of the ICG was observed in the viable region. On the contrary, there was a lower enhancement in the nonviable region.